Derecho humano a la alimentación y cuestión periurbana. Una reflexión desde la soberanía alimentaria - Marichal, María Eugenia (Universidad Nacional del Litoral, 2021)
This work analyses the potential of the food sovereignty concept to vindicate the peri-urban sector's role in food policies. For the last decades in Argentina, these policies were based on welfare and top-down conception conceived in an emergency context. This conception postponed the necessary integration and long term approach. As a hypothesis, it is proposed that this type of policies contributes to strengthen the peri-urban territories marginality as passive recipients of social benefits. In responding to a basic level of human right to food, they limit the participative, productive and ecological potential of these territories. The food sovereignty contributes to a reinterpretation of the human right to food in its most integral level, as a part of an adequate standard of living. Thus, food sovereignty enables a shift of the peri-urban from a passive consideration to its approach as a leading role in the socio-ecological transition.